Measurement of production cross-sections of natTi(p,x)43K,43,44m,44g,46g,47,48Sc,48V reactions up to 50 MeV - Dal-Ho Moon; Myung-Hwan Jung; Young Seok Hwang; Sung-Chul Yang (Nuclear Engineering and Technology, 2024)
The cross-sections of natTi(p,x) reactions were measured up to 50 MeV by using off-line γ-ray spectrometry and stacked-foil activation technique. The activation experiment was conducted using 57 MeV proton beams from the proton accelerator at the Korea Multi-purpose Accelerator Complex (KOMAC). The natNi(p,x)57Ni reaction was employed to monitor the proton beam flux. The activity of irradiated sample was measured using a high purity germanium (HPGe) detector, and the measured cross-sections were compared with literature data and the TENDL-2023 library. The present work generally matched well with the literature data. The cross-sections for 43,44,47Sc produced through the natTi(p,x) reactions can be used for medical isotopes production, while natTi(p,x)48V reaction can be utilized for proton monitoring reaction.